유전자진단에 있어서 Multiplex Ligation Dependent Probe Amplification (MLPA)의 이론과 실제 - 김구환(Gu-Hwan Kim); 이범희(Beom Hee Lee); 유한욱(Han-Wook Yoo) (Journal of genetic medicine, 2009)
Multiplex ligation dependent probe amplification (MLPA) is a PCR-based method to detect gene dosage. Since its introduction, MLPA has been used to test a large number of genes for major deletions or duplications. Genetic testing, as a diagnostic tool for genetic disease, has been used primarily to identify point mutations, including base substitutions and small insertions/deletions, using PCR and sequence analysis. However, it is difficult to identify large deletions or duplications using routine PCR- gel based assays, especially in heterozygotes. The MLPA is a more feasible method for identification of gene dosage than another routine PCR-based methods, and better able to detect deleterious deletions or duplications. In addition to detection of gene dosage, MLPA can be applied to identify methylation patterns of target genes, aneuploidy during prenatal diagnoses, and large deletions or duplications that may be associated with various cancers. The MLPA method offers numerous advantages, as it requires only a small amount of template DNA, is applicable to a wide variety of applications, and is high-throughput. On the other hand, this method suffers from disadvantages including the possibility of false positive results affected by template DNA quality, difficulties identifying SNPs located in probe sequences, and analytical complications in quantitative aspects. Multiplex ligation dependent probe amplification (MLPA)은 탐침자를 표적지에 교잡시킨 후, ligation 시키고, 그 산물을 중합효소연쇄반응으로 증폭시킴으로써 표적지의 존재여부 또는 농도를 확인할 수 있는 방법으로, 그 원리가 소개된 이래로 여러 유전자들에 대한 거대결실 및 중복돌연변이에 대한 탐색에 이용되었다. 유전자진단은 질환에 관련된 유전자에 대한 돌연변이를 탐색함으로써 질환을 진단하는 방법으로, 단일유전자 결핍 질환에 대한 유전자진단은 주로 중합효소연쇄반응과 염기서열 분석 방법을 통한 점돌연변이의 탐색에 집중되어 있다. 거대결실 또는 중복돌연변이의 경우, 특히 이형접합자를 형성하게 되는 경우는 중합효소 연쇄반응을 통하여 결실 또는 중복돌연변이 여부의 확인이 힘들다. PCR 방법에 기초하여 유전자의 농도(gene dosage)를 알 수 있는 방법으로 MLPA 방법이 소개되면서 거대결실 또는중복돌연변이를 포함하고 있던 질병 관련돌연변이들의 규명이 한층 쉬워졌다. MLPA의 원리를 응용하여 단순한 유전자의 농도 측정뿐 아니라 유전자내의 메칠화양상의 차이를 확인하거나, 염색체의 배수체 이상 등 염색체이상의 돌연변이 규명과, 전체 유전자의 크기가 비교적 커서 거대결실 돌연변이를 많이 동반하는, 주로 우성유전의 암 관련 유전자 돌연변이의 규명에 유용하게 이용된다. MLPA는 상용적인 중합효소연쇄반응으로 확인할 수 없는 유전자의 농도를 효과적으로 규명할 수 있는 방법으로, 적은 양의 주형 DNA만을 사용하고, 한가지의 실험원리로 다양한 응용이 가능하며 high-throughput이 가능한 장점을 가지는 반면, 주형 DNA의 질에 결과의 의존도가 높고, 민족 또는 개인간의 차이를 보일 수 있는 표적 DNA 염기서열 내의 single nucleotide polymorphism (SNP) 등으로 인해 분석의 오류가 생길 수 있으며, 양적 차이를 규명하는 것이므로 수 차례의 대조군 검사가 함께 진행되어야 하는 단점이 있다. 여기서는 MLPA를 이용하여 질병유전자의 돌연변이를 밝힌 사례를 바탕으로 MLPA의 원리와 탐색할 수 있는 돌연변이의 종류, 그리고 이 방법의 장단점에 대해 고찰해 보고자 한다.